Kemampuan Bahasa Arab dalam Pandangan Perilaku Keagamaan dan Kemampuan Menulis Arab (Kha>t) - Dedi Mustofa (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2019)
Writing is one of the very penting.melalui language skills to write someone will be able to more easily convey the message in writing and can understand and remember the message from a script or text. However, writing the Arabic language itself is inseparable from the ability to master handwriting. Without an understanding of khat good, allows a person to experience an error in writing the Arabic alphabet even in understanding the message of an Arabic text. The purpose of this study was to determine how much influence the ability of the Mastery of Arabic handwriting and religious behavior of a person.